Menyama Braya Image of Acculturation of Hinduism and Islam in Budakeling Village - I Dewa Gede Yoga; Aris Arif Mundayat; Yuyun Sunesti (International Journal of Social and Political Sciences, 2024)
This study explores the process of acculturation and tolerance between the Hindu and Muslim communities in Budakeling Village, Bali, focusing on the concept of "menyama braya" as a foundation for fostering inter-religious harmony. Bali, known for its strong Hindu traditions, is a multicultural society where religious and cultural diversity coexist. The research aims to identify how the practice of "menyama braya," which signifies mutual respect and recognition of others as kin, facilitates peaceful cohabitation and cultural exchange between these two religious communities. A qualitative research method with a descriptive approach was employed, involving non-participant observation, interviews with community leaders, and documentation analysis. The findings highlight the significant role of "menyama braya" in promoting intercultural dialogue, as reflected in the adoption of Balinese identities by Muslim residents, as well as joint practices such as the megibung (shared meals), ngejot (food charity), and participation in Subak (irrigation systems), along with the use of Balinese language and arts. These practices not only represent cultural exchange but also strengthen social bonds and religious tolerance. The study concludes that the "menyama braya" concept plays a crucial role in maintaining unity and peace among different religious communities in Budakeling Village, supporting the idea that multiculturalism thrives through mutual respect and cultural integration.